Revolutionizing grape industry - Prakash, G S; Satisha, J (Indian Horticulture, 2019)
Grape (Vitis vinifera) is important commercial fruit crop of India. Though it originated in temperate climate, it is well-acclimatized to both subtropical and tropical climate in India. It is cultivated for table, raisin, juice and wine purposes over an area of 0.125 million ha with a total production of 24.83 million tonnes. Because of earlier practice of cultivating grapes on special arbour system of training, its productivity was highest among grape-growing countries of the world way back in late 80s and 90s.